Segregation analysis of cleft lip with or without cleft palate: a comparison of Danish and Japanese data. - Chung, C S (1986)
The genetic basis of cleft lip with or without cleft palate [CL(P)] remains unresolved. The controversy on the role of a major gene is confounded with possible population differences. This study examines the issue of population differences by comparing two contrasting populations: Caucasians and Japanese. Japanese are known to have higher population incidence of CL(P) and yet lower recurrence risks among relatives. The study subjects consist of 2,998 nuclear families of the Danish population and 627 families of the Japanese population. The uniformly coded data were subjected to complex segregation analysis based on the mixed model. The analysis has revealed that the Danish data can be best explained by a combination of major gene action and multifactorial inheritance. The best-fitting model is characterized by recessive gene with displacement effect (t) of 2.7 in the standardized unit and gene frequency of .035. The heritability is estimated as .97. The transmission probability of Aa----a for the major gene is consistent with 1/2. On the contrary, the Japanese data can be best accounted for only by multifactorial inheritance with the heritability estimate of .77. No major heterogeneity could be detected between subsets of the data within the populations as grouped by types of ascertainment or mating. It is thus concluded that the observed inconsistency between the two populations is explained by a significant role of major gene in the Caucasian population, but not in the Japanese population.